(untitled) - Danesh, Arman (San Francisco, 2001)
This book is designed as an introduction to the installation and use of Linux based on Red Hat Linux 7.1 is a widely used version of Linux that is well suited to use on server systems, as well as Linux workstations and desktop computer.
Keywords: Hệ điều hành (Máy tính),Operating systems (computers)